2023
DOI: 10.1111/jcmm.17725
|View full text |Cite
|
Sign up to set email alerts
|

Overview of growth differentiation factor 15 in metabolic syndrome

Abstract: Growth and differentiation factor 15 (GDF15) is a member of the transforming growth factor‐β (TGF‐β) superfamily. GDF15 has been linked with several metabolic syndrome pathologies such as obesity and cardiovascular diseases. GDF15 is considered to be a metabolic regulator, although its precise mechanisms of action remain to be determined. Glial cell‐derived neurotrophic factor family receptor alpha‐like (GRAL), located in the hindbrain, has been identified as the receptor for GDF15 and signals through the core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…3 ). These data are consistent with previous findings that GDF-15 levels raise significantly in cardiovascular disease compared to healthy controls [ 1 , [8] , [9] , [10] ]. Therefore, we conclude that our chemiluminescence immunoassay is a reliable method for analyzing serum GDF-15 concentration in clinical and in vivo studies.…”
Section: Methods Validationsupporting
confidence: 93%
“…3 ). These data are consistent with previous findings that GDF-15 levels raise significantly in cardiovascular disease compared to healthy controls [ 1 , [8] , [9] , [10] ]. Therefore, we conclude that our chemiluminescence immunoassay is a reliable method for analyzing serum GDF-15 concentration in clinical and in vivo studies.…”
Section: Methods Validationsupporting
confidence: 93%
“…Johnen et al [32] observed that after 6 months of a HFD, ApoE(−/−) mice overexpressing GDF15 had smaller atherosclerotic lesions. The protective effect of GDF15 on the cardiovascular system has also been confirmed by many studies [33,34]. These findings suggest that GDF15 may help counteract some of the detrimental effects of obesity on the cardiovascular system.…”
Section: The Relationship Between Gdf15 and Weight Changementioning
confidence: 53%
“…Growth differentiation factor 15 (GDF15) has been implicated in aging, inflammation, mitochondrial dysfunction, cachexia, and sarcopenia ( 34 , 35 ). It is likely that these changes are also altered in patients with sarcopenic obesity; however, this needs to be confirmed.…”
Section: Pathogenesis Of Sarcopenic Obesitymentioning
confidence: 99%